South African physiotherapists' perception of rehabilitation - C. J. Eales; L. Nowitz; B. Montona (AOSIS, 1993)
In response to questions in an editorial comment by L Davids in the South African Journal of Physiotherapy in February 1991, a questionnaire was sent out to 450 physiotherapists to determine their perception and understanding of rehabilitation. Respondents were also requested to define rehabilitation. The questionnaire was completed by 131 physiotherapists, giving a response rate of 29%. On analysis of the questionnaire it became evident that the respondents had a limited and superficial understanding of rehabilitation. Despite this, they were of the opinion that a large percentage of their work involved rehabilitation, and they were in fact, the most important members of the rehabilitation team. In view of the findings of the questionnaire the authors agree with Davids that more attention and effort should be devoted to the "rehabilitation scene".